On Cayley isomorphisms of left and right groups - Ruangnai M. (2014)
In this paper, we investigate the characterization of CI-graphs on Cayley digraphs of left groups. We also determine which Cayley digraphs of right groups with given connection sets are CI-graphs. © 2012 Academic Publications, Ltd.